First-line osimertinib for leptomeningeal metastasis from lung adenocarcinoma with EGFR mutation as the initial and solitary site of postoperative recurrence - Ono, Yuki (Int Cancer Conf J, 2020)
Leptomeningeal metastasis (LM) from lung cancer has poor prognosis, and effective therapy has not been established. We present the case of a 54-year-old man with LM from lung adenocarcinoma harboring EGFR L858R point mutation, who received osimertinib as first-line therapy. He had previously undergone left lower lobectomy and lymph node dissection for lung adenocarcinoma. Five years and 9 months after the operation, he developed symptoms of dizziness, lightheadedness, and headache. Magnetic resonance imaging showed high signal intensity in the cerebral sulcus and meninges, and cerebrospinal fluid (CSF) cytology indicated adenocarcinoma with EGFR L858R point mutation, which suggested LM. After CSF drainage and administration of corticosteroid and glycerol, the patient received osimertinib (80 mg/day) as first-line therapy. These symptoms including dizziness, lightheadedness, and headache were relieved and the MRI appearance was normal, and he survived for 19 months with no disease progression. Osimertinib is considered to be an effective therapeutic option for LM from lung adenocarcinoma harboring EGFR mutation.